The Artemas Ward papers - Ward, Artemas, 1727-1800.; Allis, Frederick Scouller, 1913-; Pruitt, R. Bruce; Massachusetts Historical Society; United States. National Historical Publications Commission (Boston, Mass. : Massachusetts Historical Society, 1967)
Reproduces personal and family correspondence, diary (1758), orderly book, official documents, accounts, receipts, and other papers of Artemas Ward, Revolutionary War general and member of the Continental Congress; together with personal and official papers of Nahum Ward (1684-1754) concerning his duties in local offices of Shrewsbury, diaries (1827-1853) of Thomas W. Ward, correspondence of the Perry and Ward families, and genealogies, photographs, and other records of the family. Artemas Ward's papers relate to his participation in campaigns at Ft. Edward and Ft. Ticonderoga, the siege of Boston, and as head of the Eastern Department, Continental Army; his duties as Shrewsbury official and speaker of the Massachusetts House; his term as a member of the Board of Overseers at Harvard College; his activities with the Continental Congress concerning political, state, and federal affairs; and to Shay's Rebellion.
Filmed from the collections of the Massachusetts Historical Society.
Accompanied by a printed guide, entitled: Guide to the microfilm edition of The Artemas Ward papers (30 p. ; 23 cm.)
Keywords: Ward, Artemas, -- 1727-1800 -- Archives; United States -- History -- Revolution, 1775-1783 -- Sources; Massachusetts -- History -- Revolution, 1775-1783 -- Sources